An Emerging Scholarly Form: The Digital Monograph - Massimo Riva (DigitCult@Scientific Journal on Digital Cultures, 2017)
Two recent initiatives, in the English-speaking world, are currently promoting monograph publishing in digital formats, with a specific focus on the arts and humanities but also including the social sciences. The American initiative is funded by the Andrew W. Mellon foundation; in the U.K., the Arts and Humanities Research Council has also promoted a similar initiative, the Academic Book of the Future, which produced a final report released in Spring 2017. This article describes some of the challenges and opportunities the author and his team are facing in designing a digital monograph on eigteenth and nineteenth-century visual culture, one of two pilot projects of the Brown University library Digital Publishing Initiative, funded by the Mellon foundation.